2009
DOI: 10.1186/1471-2407-9-242
|View full text |Cite
|
Sign up to set email alerts
|

A novel chalcone derivative which acts as a microtubule depolymerising agent and an inhibitor of P-gp and BCRP in in-vitro and in-vivoglioblastoma models

Abstract: BackgroundOver the past decades, in spite of intensive search, no significant increase in the survival of patients with glioblastoma has been obtained. The role of the blood-brain barrier (BBB) and especially the activity of efflux pumps belonging to the ATP Binding Cassette (ABC) family may, in part, explain this defect.MethodsThe in-vitro activities of JAI-51 on cell proliferation were assessed by various experimental approaches in four human and a murine glioblastoma cell lines. Using drug exclusion assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 30 publications
2
56
0
Order By: Relevance
“…To date, the influx of Rhodamine 123, JAI-51, calceine, doxorubicin, and daunorubicin have been evaluated using such methods and are still used in drug-drug interaction studies [59]. The same technique has been used with mitoxantrone to assess transport by, and inhibition of, ABCG2.…”
Section: Cell-based Assaysmentioning
confidence: 98%
“…To date, the influx of Rhodamine 123, JAI-51, calceine, doxorubicin, and daunorubicin have been evaluated using such methods and are still used in drug-drug interaction studies [59]. The same technique has been used with mitoxantrone to assess transport by, and inhibition of, ABCG2.…”
Section: Cell-based Assaysmentioning
confidence: 98%
“…A trimethoxychalcone derivative was detected in implanted glioblastoma tumors and in the brain of i.p. treated mice, showing that at least this specific chalcone crosses the BBB (Boumendjel et al 2009). Previously, we used a computational approach to predict some pharmacokinetic parameters that helped us select the most promising compounds to assay in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that chalcone (10) provided two distinct cytoprotective mechanisms, depending on the duration of pre-treatment. Initially, chalcone (10) abrogated time and dose dependently the activation of signal transducer and activator of transcription (STAT)3 and NF-jB in IL-6 and lipopolysaccharide (LPS)- stimulated endothelial cells via depletion of intracellular glutathione (GSH) levels. Prolonged chalcone treatment (after 6 h and 12 h), however, rescued the intracellular GSH level, indicating the activation of thiol-related genes.…”
Section: Inflammation Cell-signaling Pathways Targeted By Chalconesmentioning
confidence: 99%
“…Although there are few known inhibitors of tubulin assembly among naturally occurring chalcones, a large library of chalcone analogues was synthesized. Many showed convincing antimitotic properties as microtubuledepolymerizing agents with IC 50 values of sub-lM and low lM concentrations (see Table 1) [10,31,69,87].…”
Section: Chalcones As Inhibitors Of the Cell Cyclesmentioning
confidence: 99%